Extraction of explosive compounds from aqueous solutions by solid phase extraction using β-cyclodextrin functionalized carbon nanofibers as sorbents. Issue 2 (June 2016) - Tavengwa, Nikita Tawanda; Hintsho, Nomso; Durbach, Shane; Weiersbye, Isabel; Cukrowska, Ewa; Chimuka, Luke
Graphical abstract: Highlights: The synthesis of carbon nanofibers (CNFs) from abundant waste fly ash and its functionalization with β-cyclodextrin were outlined. The β-CD@CNFs composite material was used as a sorbent in solid phase extraction for the removal of six selected nitroaromatic compounds (NACs). The sorbent was applied to spiked real samples and good recoveries of six explosive compounds were obtained. The developed method can be used for trace analysis as low detection limits (3.8–23.1 μg L −1 ) of the six explosive compounds were found. Abstract: This work describes the synthesis of carbon nanofibers (CNFs) which was functionalized with β-cyclodextrin (β-CD). The resultant composite, β-CD@CNFs, was then used for the extraction of selected nitro-based explosive compound pollutants from aqueous solutions. The extraction was through an off-line solid-phase extraction (SPE) procedure followed by high-performance liquid chromatography with ultraviolet detection. Scanning electron microscopy (SEM) and thermogravimetric analysis (TGA) were used to characterize the synthesized materials. Three independent variables: SPE elution solvent, sample pH and sample volume were investigated to determine their influence on the adsorption of the explosive compounds from aqueous samples. The breakthrough volume of 40 mL was considered as optimum. Under the optimized conditions, good calibration linearities were obtained in the range 30–150 μg L −1 with coefficients of determination (R 2 ) > 0.997 for 3-nitrotoluene (3-NT), 1, 3-dinitrobenzene (1, 3-DNB), 2, 6-dinitrotoluene (2, 6-DNT), 4-nitrotoluene (4-NT), nitrobenzene (NB) and 2-nitrotoluene (2-NT). Low limits of detection of 3.3, 7.1, 8.6, 9.7, 23.1 and 13.0 μg L −1 were found for the respective compounds. The applicability of the developed method using β-CD@CNF as a sorbent was investigated using spiked real water samples collected within the vicinity of an operational gold mine and recoveries of 36.6–102.2% were obtained.